Cognitive behavioral therapy for anxiety and depression symptoms in people of Parkinson’s disease: a systematic review and meta-analysis - Yu, Xing; Wu, Qianhao; Liu, Yuewen; Han, Peipei; Chen, Xiaoyu; Guo, Qi (Frontiers in Aging Neuroscience, 2025)
ObjectivesWe aim to conducted a systematic review and meta-analysis of published RCTs (Randomized Controlled Trials, RCTs) to quantify the effects of CBT (Cognitive behavioral therapy, CBT), including both remote and in-person modalities, on anxiety, depressive symptoms, and QoL (Quality of Life, QoL) in people with PD (Parkinson’s disease, PD).MethodsThe systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Eight databases were systematically searched for existing RCTs of CBT in people of PD published in English or Chinese. Searches were updated to February 29, 2024. Methodological quality was appraised with the Cochrane Risk of Bias tool. A meta-analysis of comparative effects was performed using the Review Manager v. 5.4 software.Results16 RCTs were included in the study. The studies involved a total of 682 participants, the mean age of participants ranged from 43 to 85. Depression scores of people in the CBT intervention group were significantly improved (SMD: −1.01, 95CI [−1.27, −0.74], P < 0.001), the overall meta-analysis result showed that the CBT group had significant improvement in anxiety compared to the control group (SMD: −2.00, 95CI [−2.74, −1.26], P < 0.001), results did not show a significant improvement in QoL in CBT group (SMD: −0.40, 95CI [−0.84, 0.04], P = 0.08).ConclusionThis systematic review and meta-analysis provide evidence that CBT intervention significantly improved anxiety and depression in People of PD compared to the control group, whether through offline or remote intervention. No improvement effect of CBT intervention on the QoL of People of PD was found. In the future application of telemedicine, interdisciplinary interventions should be explored to improve the motor and non-motor symptoms and QoL of People of PD.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails. Identifier: CRD42024526608.